Oil Extraction from Hemp Plant as a Potential Source of Cannabidiol for Healthy Protein Foods - Olga Mileti; Noemi Baldino; Mario F. O. Paleologo; Francesca R. Lupi; Maria Marra; Domenico Iacopetta; Domenico Gabriele (MDPI AG, 2023)
In recent years, the increasing demand for alternative foods has shifted research toward new sources enriched with nutraceutical molecules. It is well known that many diseases are caused by oxidative stress; thus, the supplementation of antioxidants has been proposed to reduce it. Cannabis sativa L. is an interesting species that could provide an alternative source of antioxidants. This work aimed to investigate the possibility of optimizing the yield of cannabidiol (CBD) and recovering it from residual biomass (stalks), valorizing the residual biomass, and using this for protein bar preparation. Different extraction methods were used, and High-Pressure Liquid Chromatography (HPLC) analysis was used to analyze the extracts. Antioxidant power was investigated using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assays. The best results in terms of CBD yield were obtained via dynamic maceration after decarboxylation with a quantity of 26.7 ± 2 mgCBD/graw material from inflorescences. The extract also shows good antioxidant power with an IC50 value of 38.1 ± 1.1 µg/mL measured using the DPPH assay. The CBD extract was added to the hemp oil to obtain dough for protein bars. The doughs were studied by taking rheological and technological measurements, and it was found that the protein bars could provide an excellent means for the consumption of products enriched with antioxidants because their CBD anti-inflammatory activity is preserved after cooking.